2017
DOI: 10.1590/abd1806-4841.20174964
|View full text |Cite
|
Sign up to set email alerts
|

Increased salivary aldehyde dehydrogenase 1 in non-reticular oral lichen planus

Abstract: BackgroundOral lichen planus is a potentially malignant disorder. One of the malignant transformation markers is cancer stem cells. One of the proposed marker for the detection of cancer stem cells's in head and neck cancer is aldehyde dehydrogenase. Recently it is shown that aldehyde dehydrogenase 1 expression in tissue samples is associated with oral lichen planus malignant transformation.ObjectiveThis study evaluates salivary aldehyde dehydrogenase 1 in oral lichen planus.MethodThirty patients and 30 age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The results are tabulated in Tables 1 and 2 . [ 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…The results are tabulated in Tables 1 and 2 . [ 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…ALDH expression has a direct relationship with the stage of head and neck cancer, and has a negative relationship with this is the prognosis. This biomarker plays a significant role in the metabolism of many molecules, causing detoxification of internal and external substances including alcohol and toxins (15). Oxidative stress results in carcinogenesis, which occurs due to an imbalance between the production of reactive oxygen species and the production of nitrogen species and antioxidant protective system.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress results in carcinogenesis, which occurs due to an imbalance between the production of reactive oxygen species and the production of nitrogen species and antioxidant protective system. Recent theory has shown that signals that are produced due to chronic stimulations of inflammatory and stromal cells cause uncontrolled growth of epithelial cells along with oxidative stresses (1,2,15). These stresses lead to the production of oxidative and nitrative products, causing DNA damage, eventually bringing about neoplastic changes (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral lichen planus (OLP), a precancerous lesion illness classified by the World Health Organization, is a common chronic mucocutaneous disease. 1 This inflammatory disorder has an immunological basis. It affects approximately 0.5% to 2.2% of the population and is more frequently observed in women than men.…”
Section: Introductionmentioning
confidence: 99%